Cardiovascular Autonomic Neuropathy Contributes to Sleep Apnea in Young and Lean Type 1 Diabetes Mellitus Patients - Janovsky, Carolina Castro Porto Silva; Rolim, Luiz Clemente de Souza Pereira; Sá, João Roberto de; Poyares, Dalva; Tufik, Sergio; Silva, Ademir Baptista; Dib, Sergio Atala (Frontiers in Endocrinology, 2014)
Sleep apnea in type 1 diabetes mellitus (T1DM) is a crescent theme of discussion. In obese patient, it is explained by the excessive central adiposity, including large neck circumference. Its presence in nonobese patients, however, brings back its possible correlation with autonomic neuropathy. The aim of this study was to compare the prevalence of OSA in young and lean T1DM, with and without cardiovascular autonomic neuropathy (CAN). We studied 20 adult, nonobese, type 1 diabetic patients, divided in two groups according to the results of the cardiovascular autonomic reflex tests (CARTs). These two groups (9 with CAN and 11 without CAN) were compared to a control group of 22 healthy individuals, matched by age and BMI. A polysomnography was performed and sleep was analyzed. The CAN+ group presented significantly higher prevalence of sleep apnea compared to the other groups (67% CAN+; 23% CAN-; 4,5% controls: CAN+ vs Control; p=0.00017 and CAN+ vs CAN-; p=0.02). As it was expected, the incidence of sleep apnea was correlated with more microarousals during sleep and excessive daytime sleepiness. The CAN- group showed a better sleep efficiency compared to the CAN+ group, demonstrating impaired sleep architecture in diabetics with this chronic complication. In conclusion, sleep apnea could not only be an indication of presence of CAN, but also a contributor to diabetic neuropathy impairment, causing both worse prognosis and reduced quality of life for these patients when not treated.